(untitled) (Western Journal of Medical and Biomedical Sciences, 2025)
Atorvastatin is widely used for dyslipidaemia and cardiovascular disease prevention, yet interindividual variability in efficacy and adverse effects, particularly statin-induced myopathy,limits its clinical use. Pharmacogenetic studies have largely focused on SLCO1B1 and CYP3A4/5; the role of ABCB1, which encodes P-glycoprotein, remains underexplored. This review aims to systematically evaluate the influence of ABCB1 polymorphisms on atorvastatin pharmacokinetics, efficacy, and safety outcomes. Following PRISMA guidelines, clinical studies involving adults on atorvastatin therapy will be identified from PubMed, Web of Science, and Scopus. Eligible studies must assess associations between common ABCB1 variants (e.g., C3435T, G2677T/A, and C1236T) and atorvastatin response outcomes. Data on study design, population, demographics, genotyping, and other key findings will be extracted. The risk of bias will be assessed using the Newcastle-Ottawa Scale for observational studies, and a meta-analysis will be performed. The review will clarify the contribution of ABCB1 polymorphisms to atorvastatin pharmacokinetics, lipid lowering efficacy, and adverse events. It will also explore ethnic differences in allele frequencies and treatment response. By addressing this overlooked aspect of statin pharmacogenetics, the insights gained may support the integration of ABCB1 genotyping into clinical decision-making and enhance personalised cardiovascular therapy.